2013
DOI: 10.1371/journal.pone.0085032
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A Induces Endothelial Inflammation in Systemic Sclerosis via the ERK Signaling Pathway

Abstract: Recent reports have demonstrated that endothelial cells are involved in vascular inflammatory injury in systemic sclerosis (SSc) and interleukin-17A (IL-17A) plays a crucial role in the pathogenesis of SSC. However, little is known about the effects of IL-17A on endothelial cell inflammation in SSC. The aim of our study was to investigate the role of IL-17A in endothelial inflammation. Here, we showed that IL-17A mRNA and protein levels were augmented in the peripheral blood and more IL-17+ lymphocytes infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 35 publications
4
56
0
1
Order By: Relevance
“…On the other hand, human lung microvascular ECs do appear to express IL-17RA and respond to IL-17 activation, although the magnitude of the responses observed while comparable to TNF in this cell type, are quite weak by comparisons to TNF responses in other studies (26, 27). It has also been reported that HUVECs expressed CCL20 and adhesion molecules (ICAM-1 and VCAM-1) after IL-17 stimulation, but the magnitude of expression observed in this study was again very limited (28). These data cumulatively suggest that while some EC types may respond to IL-17, the magnitude of the human EC response is very small and unlikely to account for the powerful role that IL-17 exhibits in neutrophilic inflammation.…”
Section: Discussionsupporting
confidence: 42%
“…On the other hand, human lung microvascular ECs do appear to express IL-17RA and respond to IL-17 activation, although the magnitude of the responses observed while comparable to TNF in this cell type, are quite weak by comparisons to TNF responses in other studies (26, 27). It has also been reported that HUVECs expressed CCL20 and adhesion molecules (ICAM-1 and VCAM-1) after IL-17 stimulation, but the magnitude of expression observed in this study was again very limited (28). These data cumulatively suggest that while some EC types may respond to IL-17, the magnitude of the human EC response is very small and unlikely to account for the powerful role that IL-17 exhibits in neutrophilic inflammation.…”
Section: Discussionsupporting
confidence: 42%
“…Besides its direct effects on G-CSF-mediated mobilization of neutrophils from the bone marrow, IL-17A may also contribute to neutrophil homing to the kidney by stimulating expression of adhesion molecules (e.g. VCAM-1 and E-Selectin) on the renal endothelium 77,78 . While under steady state conditions, phagocytosis of neutrophils downregulates IL-23 and subsequently IL-17-triggered neutrophil recruitment, 70 the upstream pathways that regulate IL-17A expression in response to UV light are yet to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…Both insulin and IGF1 have been found to induce VCAM-1 expression in the vascular endothelial cells [23,24]. IL-17 can also increase expression of adhesion molecules, including intercellular adhesion molecule-1 (ICAM-1), VCAM-1 and E-selectin in the endothelial cells [25,26]. It has been shown that insulin can augment tumor necrosis factor-a (TNF-a)-induced expression of VCAM-1 in the endothelial cells [27].…”
Section: Introductionmentioning
confidence: 99%